The Moral Economy: Why Good Incentives Are No Substitutefor Good Citizens (excerpts) - Bowles, Samuel (Journal of Economic Sociology, 2016)
The Moral Economy is based in part on Castle Lectures given by Prof. Samuel Bowles at Yale University that resulted from his concerns about the cultural effects of markets and incentives over 30 years. In his book, Bowles focuses on a new policy paradigm, which proposes switching from Homo economicus to an approach considering people as they are. According to Bowles, the latter approach makes synergy between incentives and constraints as well as the conjunction of ethical and other-regarding motivations possible. The author argues that only market economies that do not ignore their cultural background and the goodness of people are able to work properly. The Journal of Economic Sociology has published the first chapter, “The Problem with Homo Economicus,” in which the author tries to convince readers that the principle of Homo economicus is not a good baseline assumption for policy-making and business management for at least two reasons. First, instrumental incentives do not guarantee good government. Second, a policy, which relies on self-interested and amoral humans, creates conditions for the dominancy of this human behavior model in the real world. The author addresses a wide variety of philosophical, political, and economic literature to construct his arguments. The book is very easy to read thanks to the vivid examples and attractive anecdotes it contains.